ILAE neuroimaging task force highlight: MRI detection of early life epilepsy caused by focal cortical dysplasia - Cohen, Nathan T.; Vezina, L. Gilbert; Oluigbo, Chima; Anwar, Tayyba; Archer, John; Bernhardt, Boris C.; Caciagli, Lorenzo; Cendes, Fernando; Chinvarun, Yotin; Concha, Luis; Federico, Paolo; Kobayashi, Eliane; et al. (Epileptic Disorders, 2025)
The ILAE Neuroimaging Task Force aims to publish educational case reports that highlight basic aspects of neuroimaging in epilepsy consistent with the ILAE's educational mission. Here, we describe a case series of three neonates with focal cortical dysplasia (FCD)-related drug-resistant epilepsy who underwent surgical intervention. The purpose of this series is to demonstrate the difficulties of identifying FCD in this age group and to highlight the potential added value of arterial spin labeling MRI for delineation of the epileptogenic zone. This series also supports the importance of the 2019 ILAE recommendations for structural imaging in epilepsy, the 2009 ILAE recommendations on imaging infants and children with recent-onset epilepsy, and the 2022 ILAE consensus classification of FCD.
CRIS-Team Scopus Importer:2025-05-16
Keywords: arterial spin labeling; ASL; drug-resistant epilepsy; focal cortical dysplasia